Biomechanical behavior of cavity design on teeth restored using ceramic inlays: An approach based on three-dimensional finite element analysis and ultrahigh-speed camera. (15th April 2019) - Cheng, Chun-Wen; Chen, Weng-Pin; Chien, Yu-Ting; Teng, Yu-Ting; Lu, Pei-Ying; Huang, Shih-Hao; Lin, Po-Yen; Chiang, Yu-Chih
Graphical abstract: Abstract: Ceramic fracture and debonding are the primary failures that follow ceramic inlay and can lead to stress and tooth fracture. In this study, we examined two designs—concave and flat—of the gingival cavity bottom for tooth cavities restored using ceramic inlays. We investigated the biomechanical behavior of ceramic inlay–restored teeth (concave and flat) through three-dimensional finite element analysis (FEA) and experimentally validated the results using an ultrahigh-speed camera. We conducted in vitro real-time recording of the deformation of a restored tooth during loading using an ultrahigh-speed camera. This technique enables further image registration to observe deformation variation and vector fields. The deformation vector fields revealed that the concave design moved the deformation toward the buccal side of the cavity bottom, whereas the flat design moved it toward the palatal side. These findings correlated with the FEA results, which indicated that the concave design constrained stress in the dentin cavity and relieved palatal stress. Our results suggest that incorporating a concave design in cavity preparation can improve the fracture resistance of ceramic inlay–restored teeth, preventing unrestorable fractures. The current study is the first to utilize an ultrahigh-speed camera in dental biomechanics, and such cameras are useful for nondestructive and dynamic analysis. Statement of Significance: First utilize ultrahigh-speed cameras in dental biomechanics analysis. Tooth fracture videos captured by ultrahigh-speed camera helps us learn fracture mechanics in between tooth cavity design and ceramic inlay. Concave design leads to stress in safer areas that causes a less damaging fracture. Minimal invasive preparation by concave design strengthens tooth fracture resistance. Non-destructive data from ultrahigh-speed cameras combined with FEA can get more insight into how the stress and strain derived in biomaterials.